Calculus-related functional protein expression in ureteral calculus-adhered polyp: A preliminary study. Issue 25 (25th June 2021) - Li, Mingjie; Zhang, Heng; Jiang, Deqi; Li, Lihua; Liu, Xia; Zhao, Xiaoxiao; Ye, Dandan; Ni, Yongliang
Abstract : Abstract: To explore the expressions of calculus-related functional proteins in the ureteral calculus-adhered polyp tissues and investigate the role of these proteins in the formation of adhesions between the calculus and polyp. Patients with ureteral calculi and polyps who underwent ureteroscopic lithotripsy for the excision of polyps between January 2019 and June 2019 were enrolled. Polyps obtained from each patient were divided into 2 groups using a matched pairs design: observation group (polyps adhered to calculus) and control group (polyps not adhered to calculus). Histopathological examination of polyps was performed using hematoxylin and eosin staining. Polyp tissues were immunohistochemically stained to assess the expressions of calculus-related functional proteins, that is, annexin A1, calcium-binding protein S100A9 (S100A9), uromodulin, and osteopontin. Furthermore, quantitative analysis was performed using the H-score of tissue staining; Pearson correlation analysis was performed for proteins with high expression. Overall, 40 polyp specimens were collected from 20 patients with ureteral calculi combined with polyps (observation group, 20 specimens; control group, 20 specimens). Hematoxylin and eosin staining revealed obvious epithelial cell proliferation in polyps of both groups; crystals were observed in the epithelial cells of the polyp tissue in the observation group. The expression levels of annexin A1 and S100A9 in the observation group were significantly greater than those in the control group ( P < .05). However, no obvious expression of osteopontin or uromodulin was observed in the polyp tissues of both groups. There was a strong correlation between the increased expressions of annexin A1 and S100A9 in the observation group ( R = 0.741, P = .022). We documented increased expressions of annexin A1 and S100A9 in the ureteral calculus-adhered polyp tissues. Annexin A1 and S100A9 may play an essential role in the adhesion of calculus and polyp and the growth of calculi.